Literature Review: Pengaruh Kebijakan Dividen Dan Profitabilitas Terhadap Nilai Suatu Perusahaan - Novi Rahmadani; Desy Safitri; Ratih Kusumastuti (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
Firm value plays an important role in showing the prosperity of shareholders in the company. A company must be profitable to return its assets, shareholder equity, and sales within a certain time frame. This study aims to investigate how profitability and dividend policy impact firm value. The literature review was used in this study as a methodology, which involves collecting and analyzing findings from articles on the subject under discussion. Based on the research conducted, this study concludes that the value of a company is caused by many causes and whether dividend policy and profitability have an impact on the value of the company is still objective depending on the methods, variables, and objects used.